Pengaruh Pemanasan Bahan Bakar Terhadap Laju Konsumsi Bahan Bakar Pada Sepeda Motor Sistem Karburator - Faradila, Uswatun; Mangalla, Lukas Kano; Sudia, Budiman (Teknik Mesin Universitas Halu Oleo, 2022)
The increasing human need for transportation requires maksimum engine performance and efficient fuel consumptiton on carburetor system motorcycles. In an effort to improve engine performance it is done various ways one of which is by preheating the fuel. This study aims to determine engine performance through preheating the fuel. This research was conducted on a motorcycle with a carburetor system by providing treatment without heating and by heating the fuel with a fuel preheat temperature of 60oC, 80oC, and 90oC at 2500 rpm engine speed and the fuel used is gasoline and pertamax. In this study, fuel consumption increased at 90oC by 0,38 (Kg/hour), at 80oC and 60oC decreased by 0,30 (Kg/hour) and 0,21 (Kg/hour). Specific fuel consumption at temperature 90oC increased by 0,195 (Kg/kWh), at 80oC and 60oC decreased by 0,155 (Kg/kWh) and 0,106 (Kg/kWh) in gasoline, while in pertamax fuel, fuel consumption more efficient than gasoline, namely at a temperature of 90oC increased by 0,33 (Kg/hour), at 80oC and 60oC decreased by 0,22 (Kg/hour) and 0,19 (Kg/hour) while the specific fuel consumption at a temperature of 90oC increased by 0,170 (Kg/kWh), at 80oC and 60oC it decreased by 0,113 (Kg/kWh) and 0,095 (Kg/kWh).Kata kunci: Engine Performance, Preheating of fuel, Temperature Variations